Educational Innovation for Entrepreneurship: Results of the Pilot Implementation of the ICI Methodology in Honduras - Flores Laitano, Nidia Manuela; Pineda, Lindsay; Batres, Montserrat (LACCEI, 2025)
This study examines the implementation of the Ideation-Creation-Implementation (ICI) methodology in the Generation of Enterprises I and II courses at UNITEC, Honduras, aimed at enhancing entrepreneurial competencies among university students. Employing a mixed-methods approach, the research combined qualitative analysis of focus groups with a comprehensive literature review on entrepreneurial education and active methodologies such as Design Thinking and Lean Startup. The sample included nine students from diverse academic backgrounds who participated in the pilot experience from October 2024 to March 2025. Results indicate that the ICI methodology fosters practical, interdisciplinary learning focused on solving real-world problems, developing skills such as teamwork, empathy, critical thinking, and digital tool utilization. Challenges identified include technical limitations in digital prototyping, group coordination issues, and lack of continuity between courses. Participants especially valued early idea validation and feedback during exhibition events, which helped refine their projects. Recommendations include expanding technical workshops, improving infrastructure, and integrating curricular content to support a more comprehensive learning experience. This study provides evidence of the ICI methodology’s effectiveness as an innovative educational strategy to strengthen entrepreneurial training in structurally limited contexts, contributing to sustainable social and economic development in Honduras.